Strategies for Combating the Global Health Threat of Antibiotic Resistance: Novel Therapeutics and Combination Approaches - Twisha Senjaliya; Muskan Patel; Amar M. Raval (Asian Journal of Pharmaceutical Research and Development, 2026)
Background: Antibiotic resistance represents one of the most pressing global public health crises of the 21st century. The increasing prevalence of multidrug-resistant (MDR) bacterial pathogens has significantly reduced the clinical efficacy of existing antimicrobial therapies, resulting in prolonged hospitalizations, increased healthcare costs, and higher morbidity and mortality rates. Objective: This review critically examines the molecular mechanisms underlying antibiotic resistance and explores emerging therapeutic strategies designed to overcome resistance and restore antibiotic efficacy. Methods: A comprehensive analysis of recent scientific literature was conducted to evaluate advances in antimicrobial discovery, resistance-modifying strategies, host-directed therapies, and combination approaches. Results: Resistance mechanisms include enzymatic drug inactivation, target modification, efflux pump overexpression, permeability alterations, and horizontal gene transfer. Emerging interventions such as quorum-sensing inhibitors, bacteriophage therapy, antimicrobial peptides, nanobiotics, CRISPR-Cas systems, immunotherapeutic agents, and photodynamic therapy demonstrate promising potential in combating resistant pathogens. Conclusion: Although innovative strategies offer hope, challenges including regulatory barriers, economic limitations, and potential resistance evolution persist. A multidisciplinary, globally coordinated approach integrating antimicrobial stewardship, novel therapeutics, and policy reforms is essential to mitigate the antibiotic resistance crisis.